Tantangan implementasi rekam medis elektronik di fasilitas pelayanan kesehatan Indonesia - Anzany Tania Dwi Putri (Jurnal Medika Hutama, 2023)
The development of information and communication technology use is increasingly prominent in the health sector, including in the use of medical records. Medical records that were originally made manually are now required to evolve into electronic form, known as electronic medical records (EMR) in order to succeed digital transformation in the health system. Unfortunately, in an effort to implement EMR, it is not a quick and easy thing to do, particularly from the service provider's perspective. The aim of this article is to find out the obstacles and challenges faced by various health care providers (clinics, public health centers, and hospitals) in Indonesia. The method used is literature study using the google scholar database with inclusion criteria including review article, full text, Bahasa language, and published during 2017-2022. The result is that there are 12 articles selected to be analyzed. The challenges faced in implementing EMR are categorized into four major aspects, namely legal, human resources, infrastructure, and technology. It is hoped that the results of this literature study can be an input for the government to make policies that are able to solve the problems occurred. Thus, health digitalization in Indonesia can be optimally achieved.